Urine Phthalate Levels and Liver Function in US Adolescents: Analyses of NHANES 2007–2016 - Xiang, Shiting; Dong, Jie; Li, Xun; Li, Chao (Frontiers in Public Health, 2022)
Background Phthalates are non-persistent chemicals with endocrine-disrupting abilities widely used in a variety of consumer products. Evidence for the effects of phthalate exposure on liver function in adolescents is lacking. Methods Data were analyzed from the combined 2007–2016 National Health and Nutrition Examination Survey (NHANES). Ultimately, a total of 1,650 adolescents aged 12–19 years were selected as the samples. Weighted linear regression was used to investigate the effects of urinary phthalate metabolites on liver function indexes. Results Weighted Linear regression models showed that MCOP was negatively associated with TBIL (β = −0.0435, PFDR = 0.007), ΣDEHP (β = −0.0453, PFDR = 0.003) and MCOP (β = −0.0379, PFDR = 0.006) were negatively correlated with ALB, while MCPP was positively correlated with ALB (β = 0.0339, PFDR = 0.024), and MCOP was negatively correlated with TP (β = −0.0551; PFDR = 0.004). Conclusions Phthalate metabolites were significantly but weakly associated with changes in liver function indicators among US adolescents. Future work should further examine these relationships.